2016
DOI: 10.7358/neur-2016-019-moni
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making in adult unipolar depressed patients and healthy subjects: significant differences in Net Score and in non-traditional alternative measures

Abstract: Alterations in executive functioning are frequent in depressive patients. One clinical characteristic of depression is difficulty and slowness in decision-making. This study aimed to compare the performance of a group of 30 non-psychotic unipolar depressed to 30 healthy controls in a version of the Iowa Gambling Task (IGT) from the Psychology Experiment Building Language (PEBL). Significant differences between depressed patients and healthy controls in traditional Net Score measures as well as in various alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
2
12
0
1
Order By: Relevance
“…A basic finding of our study was that patients with SCZ, MDD, and BD all showed significant impairments of affective decision‐making ability, with the evidence of a preference to select the disadvantageous decks but not advantageous decks compared to HCs. This finding was consistent with some previous studies (Adida et al, ; E. C. Brown et al, ; Cella et al, ; Moniz et al, ; Nestor et al, ). Decision‐making was thought to be an important psychological structure of positive valence systems dimension according to Research Domain Criteria (Sanislow et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A basic finding of our study was that patients with SCZ, MDD, and BD all showed significant impairments of affective decision‐making ability, with the evidence of a preference to select the disadvantageous decks but not advantageous decks compared to HCs. This finding was consistent with some previous studies (Adida et al, ; E. C. Brown et al, ; Cella et al, ; Moniz et al, ; Nestor et al, ). Decision‐making was thought to be an important psychological structure of positive valence systems dimension according to Research Domain Criteria (Sanislow et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Participants who prefer to choose high immediate rewards and great long‐term punishments (deck A/B, disadvantageous decisions) are thought to be “short‐insighted” and impaired in reversal learning (Waltz & Gold, ; Waltz et al, ), which was inferred to be related to damages in some brain areas, such as the ventromedial prefrontal cortex, orbitofrontal cortex (Bechara, Damasio, & Damasio, ), ventrolateral prefrontal cortex (Lawrence, Jollant, O'Daly, Zelaya, & Phillips, ), and amygdala (Bechara, Damasio, Damasio, & Lee, ). Previous studies using IGT have found affective decision‐making impairments in patients with SCZ (Saperia et al, ), MDD (Moniz, Jesus, Gonçalves, Pacheco, & Viseu, ), and BD (Adida et al, ), even in subclinical individuals (van Honk, Hermans, Putman, Montagne, & Schutter, ).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Geographic heterogeneity can be observed in these studies, since 2 studies took place in the USA, 15 , 16 1 in Hungary, 17 1 in the United Kingdom, 18 and 1 in Portugal. 19 The samples of all of the selected studies can be considered relatively small, ranging from 39 to 96 participants. Patients and controls did not differ significantly in relation to gender, age or education level in each study.…”
Section: Resultsmentioning
confidence: 99%